2010
DOI: 10.3844/ijrnsp.2010.21.24
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Behavior in Intensive Care Unit

Abstract: Problem statement: In order to support the needs of the staff working in discrete areas of nursing, the attitudes, behaviors and needs of the group must first be articulated. Unfortunately, there has been little research conducted to understand the culture of what it is that health care workers think and feel and why they make the choices they do in their working environment and also why they chose to leave the environment. Specifically, what do intensive care clinicians think about the work they do when manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In Canada, the prevalence of major and minor depression among elderly were 2.6 and 4% and were higher for females, specifically those in institutions (Ostbye et al, 2005). In the United States, 20.3% of the elderly dwelling in nursing homes or institutionalized type of care were depressed (Smith, 2010). Kim et al (2009) found in their study that 66.7% of institutionalized Korean elderly and 41.7% of institutionalized Japanese elderly experienced depression.…”
Section: Introductionmentioning
confidence: 80%
“…In Canada, the prevalence of major and minor depression among elderly were 2.6 and 4% and were higher for females, specifically those in institutions (Ostbye et al, 2005). In the United States, 20.3% of the elderly dwelling in nursing homes or institutionalized type of care were depressed (Smith, 2010). Kim et al (2009) found in their study that 66.7% of institutionalized Korean elderly and 41.7% of institutionalized Japanese elderly experienced depression.…”
Section: Introductionmentioning
confidence: 80%
“…The leader has to trust the ability of employees and employees have to trust the promise of innovation of the leader. Also the research of team climate for innovation believed building a circumstance for developing creativity will be important to include trust and the feeling of safeness (Chandler et al, 2000;Ragazzoni et al, 2002;Isaksen and Lauer, 2002;Smith, 2010). Therefore, if employees feel free to have new ideas and do innovation, then it will be very critical in the trust of leader (Chandler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2 An Australian study examining end of life care in an Intensive Care Unit (ICU) described the processes and tensions involved in care provision when staff believed care to be futile. 33 The authors highlighted the lack of control many staff perceived in the ICU context and identified communication and coping strategies employed to influence clinical decision making 'upstream', engage in selfmanagement practices, and improve patient care. Ethnographic methods are ideally suited towards understanding these influences and relational dynamics that form the bases of care provision, especially given the multidisciplinary nature of palliative care.…”
Section: Opportunities For Ethnographic Research In Palliative Carementioning
confidence: 99%